Vasari e Ammannati nel cantiere della villa medicea di Castello: due disegni del Metropolitan Museum of Art di New York - Carrara, Eliana (Opus Incertum, 2019)
The article aims to show how two drawings of the Metropolitan Museum in New York, recently published and attributed to Giorgio Vasari, should be dated instead to the mid-sixties of the sixteenth century and should be interpreted as preparatory sketches for the fountain of the Apennine in the Villa Medicea di Castello, made by the painter and architect from Arezzo with the collaboration of Bartolomeo Ammannati, between 1563 and 1565. The essay also analyzes the important changes made by Vasari in the Giunti edition of The Lives to one of the introductory chapters (How Rustic Fountains are made with Stalactites and Incrustations from Water, and how Cockle Shells and Conglomerations of vitrified Stone are built into the Stucco), precisely as a result of the role played by the artist in the arrangement of the Medici gardens.